Method for preparing ni-fe or co-fe-l dh fluorinated silane surface-modified electrocatalyst, product and application

CN122959778APending Publication Date: 2026-10-23ZHEJIANG FILTER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611248549.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]耐久性严重不足:上述多重耦合效应使现有NiFe/CoFe-LDH阵列电极在1–5 A·cm-2工业电流密度下寿命通常仅数十至数百小时(多数报道<500 h),远低于AWE/AEMWE电解槽商业化要求的5000–10000 h以上耐久性门槛,成为制约GW级电解槽长期稳定运行的核心技术瓶颈

Benefits of technology

[0025]与现有技术相比,本发明针对工业级析氧反应(OER)在超高电流密度(>1–5 A·cm-2)下气泡黏附严重、传质阻塞导致过电位急剧升高与稳定性快速衰减的痛点,创新性地采用室温共沉淀法制备高比表面积NiFe/CoFe-LDH垂直纳米片阵列基底,再通过一步氟化硅烷(1H,1H,2H,2H-全氟辛基三乙氧基硅烷(PFOTES,CAS: 51851-37-7),简称PFOTES)表面修饰,实现显著疏气泡特性。Ir/Ru单原子超低负载量(0.05~0.5 wt%)下,在1M KOH中10mA·cm-2过电位≤195 mV,在3 A·cm-2超高电流密度下连续运行800 h以上活性衰减<5.5%,气泡传质阻力降低约50%。与传统水热法或无氟化修饰阵列相比,相较于水热法NiFe/CoFe-LDH无氟化修饰电极,高电流密度耐受性显著提升,工艺绿色简易、附着力强、稳定性优异,特别适用于工业AEMWE/AWE高电流密度电解槽、大规模绿氢生产及高传质需求能源转换器件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959778A_ABST
    Figure CN122959778A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method, a finished product and application of an electrocatalyst based on NiFe or CoFe-LDH fluorinated silane surface modification, and comprises the following steps: S1, dissolving Ni 2+ salt or Co 2+ salt and Fe 3+ salt in water in a molar ratio of 2-4:1, and then adding a carbonate salt; S2, stirring at room temperature, and adding a noble metal precursor solution dropwise to obtain B liquid; S3, adding an alkali solution, adjusting the pH to 9.5-11.0, and then aging, washing and drying to obtain a NiFe / CoFe-LDH array substrate; S4, immersing the obtained NiFe / CoFe-LDH array substrate in a fluorinated silane ethanol solution to perform surface fluorination modification, and finally washing and drying to obtain the electrocatalyst finished product. The vertical nanosheet array provides a high specific surface area and an open channel; the PFOTES fluorinated silane is firmly anchored to the LDH surface through a Si-O-M covalent bond, realizes a significant bubble-repellent property; the room-temperature coprecipitation ensures that the amorphous phase ratio is greater than or equal to 60%; and the Ir / Ru single-atom anchoring cooperates with the fluorinated layer to improve the bubble rapid detachment and mass transfer efficiency under a high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalytic materials technology, and in particular to a method for preparing, a product of, and an application of NiFe or CoFe-LDH fluorinated silane surface-modified electrocatalysts. Background Technology

[0002] Industrial-grade alkaline water electrolysis (AWE) and anion exchange membrane water electrolysis (AEMWE) are currently the most promising technological pathways for achieving GW / TW-scale, low-cost green hydrogen production. With the advancement of electrolyzers towards ultra-high current densities (1–5 A·cm⁻¹), [further development is needed]. -2 To significantly improve hydrogen yield, reduce unit hydrogen production costs (target <2 USD / kg H2), and increase system energy conversion efficiency (>70–75% system level), the massive O2 bubbles generated during the oxygen evolution reaction (OER) have become one of the most severe challenges restricting the actual performance of catalysts and the long-term reliability of electrolyzers. This problem is particularly prominent on non-noble metal layered double hydroxide (LDH) array electrodes, such as NiFe-LDH and CoFe-LDH, which are currently recognized as having the highest alkaline OER activity.

[0003] Existing NiFe-LDH / CoFe-LDH vertical nanoarray electrodes, although exhibiting low current densities (10–100 mA·cm⁻¹) in the laboratory, -2 Under these conditions, extremely low overpotentials (η) can be achieved. 10 (Typically <220–250 mV), but when the current density jumps to industrial level 1–5 A·cm -2 At this time, its surface bubble-promoting properties (bubble contact angle is typically <90°, bubble adhesion >10μN) lead to the following fatal chain failure mechanism: Large-scale bubble adhesion and blockage: Under ultra-high current density, the instantaneous gas production rate of OER is extremely high (several to tens of milliliters of O2 are generated per square centimeter of electrode area per second). A large number of microbubbles (initially <10μm) rapidly aggregate on the bubble-loving surface into large bubbles with diameters of tens to hundreds of micrometers. These bubbles firmly adhere to the nanosheet surface, array gaps, and three-phase interfaces, forming a continuous "gas film" or "gas bridge". The effective active site coverage can be as high as 50-80%, directly blocking the rapid supply channels of OH⁻ / H₂O to the interface and the escape path of O₂.

[0004] A sharp increase in mass transfer resistance and polarization loss: Bubble adhesion leads to severe local depletion of OH⁻ (the pH of the interfacial microenvironment can drop rapidly from 14 to <11 or even close to neutral), triggering severe concentration polarization, ohmic polarization, and gas-liquid two-phase flow resistance. This causes the actual OER overpotential to increase by more than 300–600 mV compared to the theoretical value, and the electrolyzer voltage to rise rapidly (>2.0–2.5 V@1–2 A·cm). -2Energy efficiency decreased significantly.

[0005] Localized heat accumulation and structural damage: Adhesive bubbles hinder the convective cooling of the electrolyte, further concentrating the local current density (up to tens of times the average value), generating significant Joule heating (local temperatures can rise by 20–50°C or even higher), exacerbating catalyst thermal stress, layer peeling, metal dissolution (accelerated loss of Ni / Fe / Co), irreversible phase transition (LDH → inert oxide or hydroxide aggregates), and lattice collapse induced by excessive accumulation of oxygen vacancies, ultimately leading to large-area peeling of the catalyst layer, membrane contamination, or electrode failure.

[0006] The durability is severely inadequate: the aforementioned multiple coupling effects cause existing NiFe / CoFe-LDH array electrodes to have insufficient durability at 1–5 A·cm⁻¹. -2 Under industrial current density, the lifespan is typically only tens to hundreds of hours (most reports <500 h), far below the durability threshold of 5000–10000 h required for the commercialization of AWE / AEMWE electrolyzers, becoming a core technical bottleneck restricting the long-term stable operation of GW-level electrolyzers.

[0007] To alleviate the bubble adhesion problem, existing superaerophobic strategies mainly include: laser / chemical etching to construct high-curvature micro / nano rough structures, plasma treatment to introduce fluorinated / silanized low surface energy layers, and post-coating / impregnation with fluorinated polymers (such as PTFE, FAS) or superhydrophilic oxide shells. While these methods can increase the bubble contact angle to >150° and reduce adhesion to <5μN in the laboratory, they generally suffer from the following fatal flaws, making it difficult to meet the stringent requirements of industrial applications: Poor adhesion and easy to fall off: The low surface energy layer formed by physical etching or post-spraying has weak bonding force with the LDH substrate. Under conditions of high current density, severe bubble scouring, mechanical vibration, temperature fluctuation or long-term alkaline immersion, it is very easy to peel off, crack or dissolve, resulting in rapid loss of superhydrophobic bubble properties. Complex process and high cost: It relies heavily on specialized equipment (laser etching machine, plasma instrument, precision spraying system), multi-step post-processing, vacuum / high temperature conditions or organic solvents, which increases production costs, reduces reproducibility, and is not conducive to uniform and large-scale preparation on three-dimensional porous current collectors (such as nickel foam, carbon cloth, metal mesh). The contradiction between compatibility and stability: However, the stability of fluoride coatings in strong alkalis varies depending on their specific chemical composition and cannot be generalized: (a) Fluoropolymer coatings (such as PVdF) do indeed face the risk of defluorination degradation under alkaline conditions; (b) Metal fluoride coatings (such as MgF2 and AlF3), while chemically inert to alkalis, lack catalytic activity and require high-temperature preparation; (c) Fluorosilane coatings (such as PFOTES / FAS) precisely utilize the alkaline environment to drive the positive stabilization process of hydrolysis → polycondensation → crosslinking, forming a dense polysiloxane network, which is stable in 1–10 M KOH for a long time. Therefore, selecting the correct type of fluoride—rather than abandoning the fluorination strategy altogether—is the key to breaking through the long-life anode of industrial alkaline electrolysis. Summary of the Invention

[0008] The purpose of this invention is to provide a method for preparing NiFe or CoFe-LDH fluorinated silane surface-modified electrocatalysts, products, and applications, which can effectively solve the above-mentioned technical problems.

[0009] The technical solution of this invention: A method for preparing NiFe or CoFe-LDH fluorinated silane surface-modified electrocatalysts, comprising the following steps: S1, Ni 2+ Salt or Co 2+ Salt and Fe 3+ Salt is dissolved in water at a molar ratio of 2 to 4:1, followed by the addition of carbonate salt to obtain solution A; S2. Stir solution A at room temperature, add noble metal precursor solution dropwise, and control the noble metal loading in the noble metal precursor solution to be 0.05-0.5 wt% to obtain solution B. S3. Add alkaline solution dropwise to solution B to adjust the pH to 9.5-11.0, and precipitate at room temperature (15-30℃, preferably 20-25℃) for 2-6 hours. Then, age, wash and dry to obtain NiFe / CoFe-LDH array substrate. S4. Immerse the obtained NiFe / CoFe-LDH array substrate in a fluorinated silane ethanol solution and react for 1–4 h to perform surface fluorination modification. Finally, wash and dry to obtain the electrocatalyst product.

[0010] In the aforementioned method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification, an anionic salt is also added in step S1.

[0011] In the aforementioned method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification, the carbonate salt is Na2CO3 or (NH4)2CO3.

[0012] In the aforementioned method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification, the noble metal precursor solution is H2IrCl6 or RuCl3.

[0013] In the aforementioned method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification, in step S3, the NiFe / CoFe-LDH array substrate can also be obtained by in-situ growth on a conductive current collector after co-precipitation and aging at room temperature for 2-6 hours; the conductive current collector is nickel foam, carbon cloth, or titanium mesh.

[0014] In the aforementioned method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification, in step S4, the fluorination modification reaction is carried out at a temperature of 15-60℃.

[0015] In the aforementioned method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification, the fluorinated silane is 1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTES, CAS: 51851-37-7) with a concentration of 0.5–5 vol.

[0016] An electrocatalyst, said electrocatalyst being prepared by the aforementioned method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification.

[0017] In one of the aforementioned electrocatalysts, the finished electrocatalyst product has a vertical nanosheet array morphology.

[0018] In the aforementioned electrocatalyst, the specific surface area of ​​the electrocatalyst is ≥300 m² / g, the underwater bubble contact angle is >135°, the air-water droplet contact angle is <45°, and the amorphous region accounts for ≥60%.

[0019] The application of electrocatalysts in high current density AEMWE / AWE electrolyzers, green hydrogen production, or high current density energy conversion devices, wherein the electrocatalysts are those described above.

[0020] In this invention, the vertical nanosheet array provides a high specific surface area and open channels; PFOTES fluorinated silane is firmly anchored to the LDH surface through Si–O–M covalent bonds, forming a low surface energy fluorinated layer (significantly reducing surface energy), achieving significant bubble-repellent properties (see the PFOTES alkaline environment stabilization mechanism below); room temperature coprecipitation ensures that the proportion of amorphous phase is ≥60%, increasing active sites; Ir / Ru single-atom anchoring and the fluorinated layer work synergistically to improve the rapid bubble detachment and mass transfer efficiency under high current density. PFOTES (1H,1H,2H,2H-perfluorooctyltriethoxysilane, CAS: 51851-37-7) undergoes the following stabilization process in alkaline media, rather than simple degradation: (1) Alkaline-catalyzed hydrolysis activation—Under alkaline conditions of pH 9.5–11.0 in the reaction system, the ethoxy group (–OCH2CH3) of PFOTES undergoes catalytic hydrolysis to generate highly reactive silanol groups (Si–OH). The alkaline environment plays a key catalytic role here, rather than a degradation factor.

[0021] (2) In-situ condensation anchoring - The generated Si–OH undergoes a dehydration condensation reaction with the hydroxyl groups (–OH) on the surface of the LDH nanosheets to form a strong Si–O–M covalent bond (M=Ni, Co, Fe), which irreversibly anchors the perfluoroalkyl chain to the surface of the carrier.

[0022] (3) Crosslinking Stabilization – The Si–OH molecules between adjacent PFOTES molecules further condense to form a Si–O–Si crosslinking network, constituting a dense siloxane protective layer. At this point, PFOTES has transformed from a hydrolyzable small-molecule silane into a chemically stable polysiloxane coating, and the perfluoroalkyl chains (–CF2–CF2–…–CF3) endow the surface with extremely low surface energy. Therefore, the PFOTES coating is not only resistant to strong alkaline electrolytes (1–10 M KOH), but also relies on alkaline conditions to complete its functionalization process. Fluorosilane coatings can still maintain superhydrophobic properties after being immersed in acid, alkali, and salt solutions for 15 days, confirming their excellent chemical stability. In contrast, common fluoropolymer coatings (such as polyvinylidene fluoride PVdF) do indeed undergo defluorination degradation under alkaline conditions, so traditional post-coating / impregnation methods of fluorinated polymers are difficult to maintain for a long time in industrial alkaline electrolysis. The fluorosilane route used in this invention utilizes an alkaline environment to drive the positive stabilization process of hydrolysis-condensation-crosslinking, thus fundamentally avoiding this defect.

[0023] It is worth noting that the contact angle of water droplets in the air after PFOTES modification is measured to be 15°-21° (superhydrophilic), which is different from that of typical fluorocarbon surfaces (>100°). The physical mechanism is as follows: the siloxane end of PFOTES is covalently anchored to LDH, and the perfluoroalkyl tail extends outward. This orientation arrangement makes the surface exhibit microscopic chemical heterogeneity. The high roughness of the LDH nanoarray and the surface hydroxyl groups enable water molecules to form a strongly bound hydration layer on the surface. Bubbles cannot displace the hydration layer and directly contact the solid surface, thus exhibiting superhydrophobic properties underwater. In the underwater environment, the LDH matrix region is preferentially occupied by water molecules (forming a hydration layer), while the fluorinated region repels bubbles, causing bubbles to rapidly and spontaneously detach from the surface upon contact. This is the microscopic mechanism that increases the contact angle of bubbles underwater, and it is also the fundamental reason why this material can rapidly remove bubbles under OER conditions.

[0024] In contrast, while metal fluorides (such as MgF2 and AlF3) are chemically inert to alkalis, they lack catalytic activity and require high-temperature processing for preparation, making them unsuitable for the room-temperature OER catalyst system of this invention. Therefore, the PFOTES fluorosilane route of this invention achieves a unique balance between alkaline stability, catalytic compatibility, and process simplicity, making it a preferred strategy for optimizing anti-bubble mass transfer at the anode in industrial alkaline water electrolysis.

[0025] Compared with existing technologies, this invention targets industrial-grade oxygen evolution reaction (OER) at ultra-high current densities (>1–5 A·cm). -2 To address the pain points of severe bubble adhesion, mass transfer blockage leading to a sharp increase in overpotential and rapid decline in stability, this paper innovatively employs a room-temperature co-precipitation method to prepare a high specific surface area NiFe / CoFe-LDH vertical nanosheet array substrate. This is followed by a one-step surface modification with fluorinated silane (1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTES, CAS: 51851-37-7), abbreviated as PFOTES), achieving significant bubble-repellent properties. With ultra-low Ir / Ru single-atom loadings (0.05–0.5 wt%), the surface in 1M KOH at 10 mA·cm⁻¹... -2 Overpotential ≤195 mV, at 3 A·cm -2 The activity decay is less than 5.5% after continuous operation for more than 800 hours at ultra-high current density, and the bubble mass transfer resistance is reduced by about 50%. Compared with traditional hydrothermal methods or fluorine-free modified arrays, and compared with hydrothermal NiFe / CoFe-LDH fluorine-free modified electrodes, the high current density tolerance is significantly improved. The process is green and simple, with strong adhesion and excellent stability. It is particularly suitable for industrial AEMWE / AWE high current density electrolyzers, large-scale green hydrogen production, and energy conversion devices with high mass transfer requirements. 1. Significantly improved bubble deflating and mass transfer optimization: underwater bubble contact angle >135°, @3 A·cm -2 Mass transfer resistance is reduced by about 50%, and the overpotential increase at high current density is significantly smaller than that of traditional bubble-loving electrodes. 2. Compared with traditional hydrothermal methods or post-coating fluorination methods, the present invention completes the process by room temperature co-precipitation + one-step fluorination modification, without the need for high temperature and high pressure or complex equipment. Compared with traditional hydrothermal methods (high temperature and high pressure), the energy consumption and process cycle are significantly reduced. The fluorinated coating is firm (resistant to ultrasonic cleaning for >30 min without peeling) and not easy to peel off. 3. Amorphous phase content ≥60% (significant XRD broadening peaks), combined with vertical array and bubble-free characteristics, results in a specific surface area ≥300 m² / g and a specific surface area ≥10 mA·cm². -2 With an overpotential ≤195 mV, the high current density tolerance is significantly improved compared to the hydrothermal NiFe / CoFe-LDH fluorine-free modified electrode. 4. Stability decay of <3.9% over 1000 hours. It combines high activity and excellent mass transfer performance under ultra-low load conditions, making it suitable for industrial high current density AEMWE / AWE electrolyzers. It has significant industrial durability and economic advantages. Attached Figure Description

[0026] Figure 1 The OER polarization curves (semi-logarithmic scale, 1M KOH, 25℃) in the low current region show the results for Examples 1, 2, Comparative Example 1, and commercial IrO2 at 10 mA·cm⁻¹. -2 Overpotential comparison at the location; Figure 2 It is a 1000h constant current (10 mA·cm) -2 The LSV comparison before and after the test shows the difference in durability between Example 1 (NiFe-LDH+PFOTES) and Comparative Example 1 (without PFOTES). Figure 3 This is Example 1 ( Figure 3 a) and Example 2 ( Figure 3 b) Wettability characterization diagram (captive bubble method, 1MKOH); Figure 4 The XRD pattern of the catalyst in Example 1 shows a significant broadening of the characteristic diffraction peaks of LDH, with the amorphous phase accounting for approximately 65%. Figure 5 A comparison of FTIR spectra before and after PFOTES modification confirms the Si-OM covalent bond (980 cm⁻¹). -1 The formation of CF2 / CF3 fluorinated groups (1150-1245 cm) and the formation of CF2 / CF3 fluorinated groups (1150-1245 cm) -1 The successful introduction of ) Figure 6 It is a high current density (1-5 A·cm) -2 OER polarization curves (linear coordinates) show the differences in mass transfer performance of different catalysts at industrial-grade current densities; Figure 7 The bar chart shows the mass transfer loss of Example 1 (275 mV), Example 2 (290 mV), Comparative Example 1 (540 mV), and commercial IrO2 (480 mV) compared to the increase of mass transfer overpotential at high current density. Figure 8 It is an 800-hour constant current long-term stability test (@3 A·cm). -2 (1M KOH) to demonstrate the durability differences between Example 1 (5.2% increase), Example 2 (4.8% increase), and Comparative Example 1 (38% increase within 150h); Figure 9It is the underwater bubble contact angle under different PFOTES modification conditions (142°~155°, captive bubble method). Detailed Implementation

[0027] The present invention will be further described below with reference to the accompanying drawings and embodiments, but this should not be construed as limiting the present invention.

[0028] This application addresses the core technical pain points faced by NiFe / CoFe-LDH array electrodes in industrial alkaline water and AEMWE electrolysis at ultra-high current densities, including bubble adhesion and blockage due to bubble affinity, a sharp increase in mass transfer resistance, rapid rise in overpotential, local heat accumulation and structural damage, and severe insufficient durability. It also addresses the shortcomings of existing bubble-reducing strategies, such as poor adhesion, complex processes, and high costs. This invention proposes a novel room-temperature co-precipitation + one-step in-situ fluorinated silane modification strategy. This process achieves the following multiple synergistic breakthroughs under mild conditions of room temperature and pressure, without the need for heating or high-pressure equipment: In-situ construction of vertical array substrate: By precisely controlling the precipitation kinetics and surfactant / anion ratio, a highly ordered, ultrathin, and highly exposed vertically interconnected nanosheet array is formed in one step, which greatly improves the specific surface area, the number of three-phase interfaces, and the bubble escape channels. One-step in-situ surface modification with fluorinated silanes: After co-precipitation to obtain the array substrate, a fluorinated silane coupling agent (such as 1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTES, CAS: 51851-37-7)) is introduced by post-impregnation. By utilizing the siloxane hydrolysis-condensation reaction of silanes and the chemical bonding with the hydroxyl groups on the LDH surface, a strong, low surface energy fluorinated siloxane monolayer or ultrathin network is formed in situ on the surface / edge of the nanosheet, achieving significant bubble-repellent properties with an underwater bubble contact angle >135°. Ultimate mass transfer optimization and rapid bubble detachment: The superhydrophobic bubble interface enables O2 bubbles to detach spontaneously from the surface rapidly after formation, avoiding aggregation and adhesion; combined with the high curvature edges of the vertical array and the open pore structure, efficient and rapid bubble escape is achieved, significantly reducing mass transfer polarization and alleviating local OH stress. - Depletion and heat accumulation; High current density and ultra-long-term stability are ensured: Fluorosilanes are covalently anchored in situ to the LDH layer, avoiding the problem of easy peeling off traditional post-coatings; room temperature processing "freezes" a high proportion of amorphous / low-crystallinity phases, and the combination of the mechanical toughness of the array structure and the chemical protection of the fluorinated layer significantly improves the resistance to bubble erosion, alkali corrosion, and thermal stress, enabling the catalyst to operate at 1–5 A·cm⁻¹ for extended periods. -2 Its durability is several times to tens of times better than that of traditional systems, approaching or meeting the industrial-grade requirement of over 800 hours.

[0029] This invention employs an innovative strategy of room-temperature co-precipitation to prepare a vertical array substrate followed by one-step in-situ modification with fluorinated silanes. This strategy simultaneously optimizes high-exposure morphology, significant bubble-repellent properties, and long-term stability at industrial-grade high current densities. It provides an effective technical path for managing bubbles in ultra-high current density OERs, a key challenge that has long constrained alkaline and AEMWE / AWE water electrolysis for hydrogen production. Furthermore, it offers a green, simple, and scalable technical path for developing low-cost, high-efficiency, and ultra-long-life non-precious metal anode array electrodes, demonstrating outstanding academic innovation value and broad prospects for industrial application.

[0030] Example. A method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification, comprising the following steps: S1, Ni 2+ Salt or Co 2+ Salt and Fe 3+ Salt is dissolved in water at a molar ratio of 2 to 4:1, followed by the addition of carbonate salt to obtain solution A; S2. Stir solution A at room temperature, add noble metal precursor solution dropwise, and control the noble metal loading in the noble metal precursor solution to be 0.05-0.5 wt% to obtain solution B. S3. Add alkaline solution dropwise to solution B to adjust the pH to 9.5-11.0, and precipitate at room temperature (15-30℃, preferably 20-25℃) for 2-6 hours. Then, age, wash and dry to obtain NiFe / CoFe-LDH array substrate. S4. Immerse the obtained NiFe / CoFe-LDH array substrate in a fluorinated silane ethanol solution and react for 1–4 h to perform surface fluorination modification. Finally, wash and dry to obtain the electrocatalyst product.

[0031] In step S1, an anionic salt is also added.

[0032] The carbonate is Na2CO3 or (NH4)2CO3.

[0033] The noble metal precursor solution is H2IrCl6 or RuCl3.

[0034] In step S3, the NiFe / CoFe-LDH array substrate can also be prepared by co-precipitation at room temperature for 2-6 hours followed by in-situ growth on a conductive current collector; the conductive current collector is nickel foam, carbon cloth, or titanium mesh.

[0035] In step S4, the fluorination modification reaction is carried out at a temperature of 15-60°C.

[0036] The fluorinated silane is 1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTES, CAS: 51851-37-7), with a concentration of 0.5–5 vol.

[0037] An electrocatalyst, said electrocatalyst being prepared by the aforementioned method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification.

[0038] The electrocatalyst product has the morphology of a vertical nanosheet array.

[0039] The electrocatalyst has a specific surface area ≥300 m² / g, an underwater bubble contact angle >135°, an air-water droplet contact angle <45°, and an amorphous region ratio ≥60%.

[0040] In 1 M KOH solution, the overpotential at a current density of 10 mA·cm⁻² is ≤195 mV. After 1000 h of constant current testing at 10 mA·cm⁻² in 1 M KOH, the overpotential decay was ≤3.9%. The electrocatalyst consists of a vertical array support rich in amorphous phase NiFe / CoFe-LDH and noble metal single atoms supported thereon. The surface has a low surface energy modification layer of fluorinated silane, which has significant bubble-repellent properties. Example 1 (NiFe-LDH vertical array + PFOTES modification) Ni(NO3)2·6H2O, 2.908 g; Fe(NO3)3·9H2O, 1.616 g; Na2CO3, 0.530 g; dissolved in 100 mL deionized water, 0.6 mL of 0.01 mol / L H2IrCl6 (Ir loaded 0.24 wt%) was added dropwise at room temperature, the pH was adjusted to 10.0 with NaOH, and co-precipitation was carried out for 4 h. After aging, a NiFe-LDH array was grown in situ on nickel foam. The NiFe-LDH array was immersed in 3 vol% PFOTES ethanol solution and reacted at room temperature for 2 h. After washing and drying at 60 °C, the final catalyst was obtained. Vertical nanosheet array, specific surface area 312 m² / g; underwater bubble contact angle 150°, air-water droplet contact angle 15° ( Figure 3 a), the proportion of amorphous regions in XRD ( Figure 4 ~65%. In 1 M KOH, 10 mA·cm -2 Overpotential 193 mV, decay 3.9% over 1000 h at 10 mA·cm⁻².

[0041] The bubble wettability of the electrocatalyst surface before and after modification was characterized using an underwater bubble contact angle meter. Tests were conducted in 1M KOH electrolyte. Bubbles were introduced below the electrode surface using a microsyringe, and the contact morphology and detachment process of the bubbles on the electrode surface were recorded. After modification with PFOTES fluorinated silane, the catalyst surface exhibited superhydrophilic-bubble-repellent properties: the measured contact angle of air-water droplets was 15° (superhydrophilic). Figure 3 a) The measured underwater bubble contact angle is 150° ( Figure 3 a) The bubbles are nearly spherical on the surface with a small contact area, which allows for spontaneous and rapid detachment of the bubbles at extremely low overpotentials, effectively avoiding bubble accumulation and mass transfer blockage under high current density.

[0042] Within the PFOTES concentration range of this invention (0.5~5 vol%, corresponding to claim 7), the modification conditions (concentration, time) were adjusted, and the underwater bubble contact angle was measured to be 142°~155°. Figure 9 The air-repellency increased with the degree of modification, and was significantly higher than that of the unmodified control.

[0043] Example 2 (CoFe-LDH+PFOTES modification) Co(NO3)2·6H2O, 2.910 g; Fe(NO3)3·9H2O, 1.616 g; the remaining steps were the same as in Example 1, with Ru loading of 0.20 wt%. In 1 M KOH, the overpotential was 200 mV at 10 mA·cm⁻², and the Tafel slope was 38 mV / dec. After 800 h of testing at a constant current of 3 A·cm⁻², the working potential increased by 4.8%. After modification with PFOTES fluorinated silane, the catalyst surface exhibited superhydrophilic-bubble-repellent properties: the measured contact angle of air droplets was 19° (superhydrophilic). Figure 3 b) The measured underwater bubble contact angle is 142° (superhydrophobic). Figure 3 (b) The bubbles are nearly spherical on the surface with a small contact area, which allows for spontaneous and rapid detachment of the bubbles at extremely low overpotentials, effectively avoiding bubble accumulation and mass transfer blockage under high current density.

[0044] Comparative Example 1.

[0045] Ni(NO3)2·6H2O, 2.908 g; Fe(NO3)3·9H2O, 1.616 g; Na2CO3, 0.530 g; dissolved in 100 mL deionized water, 0.6 mL of 0.01 mol / L H2IrCl6 (Ir loading 0.24 wt%) was added dropwise at room temperature, the pH was adjusted to 10.0 with NaOH, and co-precipitation was carried out at room temperature for 4 h to obtain a NiFe-LDH array. This array was not modified with PFOTES fluorinated silane. The low-current overpotential was 260 mV (10 mA·cm²). Due to the lack of a low-surface-energy fluorinated layer, the surface anaerobicness was insufficient, and the bubble residence time on the surface was prolonged at @3 A·cm². - ²Severe bubble blockage occurs after 150 h at high current density, with performance degradation >35%.

[0046] The OER polarization curves of the catalyst in the ultra-high current density range of 1–5 A·cm⁻² were tested in 1M KOH electrolyte. Figure 6 (Linear coordinates). Example 1 (NiFe-LDH vertical array + PFOTES modification) exhibits significant mass transfer advantages in the high current region: the overpotential at @3A·cm⁻² increases by only about 275 mV compared to @10 mA·cm⁻², far lower than Comparative Example 1 (unmodified, overpotential increase of 540 mV) and commercial IrO₂ (increase of 480 mV). This is attributed to the significant bubble-repellent properties imparted by the fluorinated silane modification layer, which allows bubbles to detach from the electrode surface instantly upon formation, avoiding OH⁻ concentration polarization and mass transfer resistance caused by gas film accumulation. Figure 7 The overpotential increase of each catalyst at @3 A·cm-2 relative to @10 mA·cm-2 was compared using a bar chart. Example 2 (CoFe-LDH+PFOTES) also showed excellent performance (an increase of about 290 mV), while the unmodified catalyst experienced a sharp increase in mass transfer overpotential due to severe bubble-loving effect, resulting in a significant decrease in active site utilization.

[0047] High current long-term stability test Figure 8 ) The catalyst was subjected to 800 hours of continuous electrolysis testing under a constant current of 3 A·cm⁻². Figure 8In Example 1 (PFOTES-modified NiFe-LDH), after 800 hours of operation, the working potential only increased from the initial ~1723 mV to ~1813 mV (an increase of 5.2%), with a stable curve and no potential abrupt changes caused by bubble accumulation. Example 2 (CoFe-LDH+PFOTES) showed an increase of 4.8%. Comparative Example 1 (unmodified) experienced a severe potential surge (an increase of 38%) within 150 hours, and after 800 hours, the working potential approached 2500 mV. The nanosheets broke and collapsed due to intense bubble erosion, and the continuous bubble adhesion caused by the lack of the fluorinated layer was the fundamental reason for the performance degradation.

[0048] In summary, PFOTES fluorinated silane surface modification significantly reduces bubble adhesion at high current densities by constructing a superhydrophilic-superhydrophobic bubble interface, fundamentally solving the core problem of mass transfer failure caused by bubble blockage of active sites under industrial-grade current densities. This strategy provides a clear scientific basis and a scalable technical path for achieving long-life anodes in GW-scale alkaline / AEMWE electrolyzers.

Claims

1. A method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification, characterized in that, Includes the following steps: S1, Ni 2+ Salt or Co 2+ Salt and Fe 3+ Salt is dissolved in water at a molar ratio of 2 to 4:1, followed by the addition of carbonate salt to obtain solution A; S2. Stir solution A at room temperature, add noble metal precursor solution dropwise, and control the noble metal loading in the noble metal precursor solution to be 0.05-0.5 wt% to obtain solution B. S3. Add alkaline solution to solution B to adjust the pH to 9.5-11.0, and precipitate at room temperature (15-30℃) for 2-6 hours. Then, age, wash and dry to obtain NiFe / CoFe-LDH array substrate. S4. Immerse the obtained NiFe / CoFe-LDH array substrate in a fluorinated silane ethanol solution and react for 1–4 h to perform surface fluorination modification. Finally, wash and dry to obtain the electrocatalyst product.

2. The method for preparing an electrocatalyst based on NiFe or CoFe-LDH fluorinated silane surface modification according to claim 1, characterized in that, In step S1, an anionic salt is also added.

3. The method for preparing electrocatalysts based on NiFe or CoFe-LDH fluorinated silane surface modification according to claim 1, characterized in that: The carbonate is Na2CO3 or (NH4)2CO3.

4. The method for preparing an electrocatalyst based on NiFe or CoFe-LDH fluorinated silane surface modification according to claim 1, characterized in that: The noble metal precursor solution is H2IrCl6 or RuCl3.

5. The method for preparing an electrocatalyst based on NiFe or CoFe-LDH fluorinated silane surface modification according to claim 1, characterized in that, In step S3, the NiFe / CoFe-LDH array substrate can also be prepared by co-precipitation at room temperature for 2-6 hours followed by in-situ growth on a conductive current collector; the conductive current collector is nickel foam, carbon cloth, or titanium mesh.

6. The method for preparing an electrocatalyst based on NiFe or CoFe-LDH fluorinated silane surface modification according to claim 1, characterized in that, In step S4, the fluorination modification reaction is carried out at a temperature of 15-60°C.

7. The method for preparing an electrocatalyst based on NiFe or CoFe-LDH fluorinated silane surface modification according to claim 1, characterized in that, The fluorinated silane is 1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTES, CAS: 51851-37-7), with a concentration of 0.5–5 vol.

8. An electrocatalyst, characterized in that, The electrocatalyst is prepared by any one of the electrocatalyst preparation methods based on NiFe or CoFe-LDH fluorinated silane surface modification as described in any one of claims 1-7.

9. An electrocatalyst according to claim 8, characterized in that, The finished electrocatalyst has a vertical nanosheet array morphology; the specific surface area of ​​the electrocatalyst is ≥300 m² / g, the underwater bubble contact angle is >135°, the air-water droplet contact angle is <45°, and the amorphous region accounts for ≥60%.

10. The application of electrocatalysts in high current density AEMWE / AWE electrolyzers, green hydrogen production, or high current density energy conversion devices, characterized in that, The electrocatalyst is the electrocatalyst according to claim 9.